On Common Coupled Fixed Point Theorems for Comparable Mappings in Ordered Partially Metric Spaces - Ali Mutlu; Nermin Yolcu; Berrin Mutlu; Necdet Bildik (Abstract and Applied Analysis)
Common coupled fixed point theorems are examined in this paper for comparable mappings ensuring nonlinear contraction in ordered partial metric spaces. Given theorems enlarge and universalize some conclusions of Gnana Bhaskar and Lakshmikantham (2006).